A Systematic Review and International Web-Based Survey of Randomized Controlled Trials in the Perioperative and Critical Care Setting: Interventions Increasing Mortality - Sartini, Chiara; Lomivorotov, Vladimir; Pisano, Antonio; Riha, Hynek; Baiardo Redaelli, Martina; Lopez-Delgado, Juan Carlos; Pieri, Marina; Hajjar, Ludhmila; Fominskiy, Evgeny; Likhvantsev, Valery; Cabrini, Luca; Bradic, Nikola; et al. (Elsevier, 2019)
Objective: Reducing mortality is a key target in critical care and perioperative medicine. The authors aimed to identify all nonsurgical interventions (drugs, techniques, strategies) shown by randomized trials to increase mortality in these clinical settings. Design: A systematic review of the literature followed by a consensus-based voting process. Setting: A web-based international consensus conference. Participants: Two hundred fifty-one physicians from 46 countries. Interventions: The authors performed a systematic literature search and identified all randomized controlled trials (RCTs) showing a significant increase in unadjusted landmark mortality among surgical or critically ill patients. The authors reviewed such studies during a meeting by a core group of experts. Studies selected after such review advanced to web-based voting by clinicians in relation to agreement, clinical practice, and willingness to include each intervention in international guidelines. Measurements and Main Results: The authors selected 12 RCTs dealing with 12 interventions increasing mortality: diaspirin-crosslinked hemoglobin (92% of agreement among web voters), overfeeding, nitric oxide synthase inhibitor in septic shock, human growth hormone, thyroxin in acute kidney injury, intravenous salbutamol in acute respiratory distress syndrome, plasma-derived protein C concentrate, aprotinin in high-risk cardiac surgery, cysteine prodrug, hypothermia in meningitis, methylprednisolone in traumatic brain injury, and albumin in traumatic brain injury (72% of agreement). Overall, a high consistency (ranging from 80% to 90%) between agreement and clinical practice was observed. Conclusion: The authors identified 12 clinical interventions showing increased mortality supported by randomized controlled trials with nonconflicting evidence, and wide agreement upon clinicians on a global scale. © 2019 Elsevier Inc.